Uneven peripheral developments in Central and Eastern Europe: A case study of the Tirana city region, Albania - Mele, Marcela; Muka, Majlinda (Quaestiones Geographicae, 2022)
This paper traces residential and spatial urban transformations in Albania, one of the last post-socialist countries embracing neoliberalism. To do this, we employed a discourse analysis based on analogies of uneven urban peripheral developments in the regions of Central and Eastern Europe (CEE), evaluating the impact of uneven (sub) urban development of settlements, with a particular emphasis on socio-economic aspects that need to be addressed in the process of extensive urban growth of the Tirana city region. Our empirical analysis reveals the inherent diversity of urban experiences across post-socialist countries in CEE with a particular reference to how the new post-socialist urban landscape in the Tirana city region produces geographically uneven socio-spatial development. Additionally, we highlight the dichotomy between the urban conditions of a ‘fortress landscape’ in the southern part of the capital of Tirana and its northern part of a new emerging small municipality lagging behind (in)formally with a new fringes identity. Our findings theoretically contribute to a post-socialist critique of urban studies due to urban theory’s neglect of post-socialist cities like Tirana.